2014
DOI: 10.1088/1612-2011/11/4/045701
|View full text |Cite
|
Sign up to set email alerts
|

Stripline split-ring resonator with integrated optogalvanic sample cell

Abstract: Stripline split-ring resonator with integrated optogalvanic sample cell.Laser Physics Letters, 11(4) dating and pharmaceutical sciences. However, recent reports show that ICOGS suffers from substantial problems with reproducibility. To qualify ICOGS as an analytical method, more stable and reliable plasma generation and signal detection are needed. In our proposed setup, critical parameters have been improved. We have utilized a stripline split-ring resonator microwave-induced microplasma source to excite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…2, was almost identical to the one in [16], having a 2 mm wide gap and a resonance frequency of 2.7 GHz, although the windows were replaced by ½ inch antireflection coated ZnSe windows (WG70530-F, Thorlabs Inc., Newton, NJ, USA) glued to two ½ inch union tee fittings (SS-8-UT-3, Swagelok, Solon, OH, USA), which served as gas connectors, instead of the integrated channels. The electronics, gas handling system, and optics of the setup too resembled that of [16], where the laser beam from a single longitudinal mode 12 CO 2 laser was modulated by a chopper before being coupled through the reference and SSRR cells to a power meter. However, there were a few differences compared with the earlier setup, Fig.…”
Section: Methodssupporting
confidence: 65%
See 4 more Smart Citations
“…2, was almost identical to the one in [16], having a 2 mm wide gap and a resonance frequency of 2.7 GHz, although the windows were replaced by ½ inch antireflection coated ZnSe windows (WG70530-F, Thorlabs Inc., Newton, NJ, USA) glued to two ½ inch union tee fittings (SS-8-UT-3, Swagelok, Solon, OH, USA), which served as gas connectors, instead of the integrated channels. The electronics, gas handling system, and optics of the setup too resembled that of [16], where the laser beam from a single longitudinal mode 12 CO 2 laser was modulated by a chopper before being coupled through the reference and SSRR cells to a power meter. However, there were a few differences compared with the earlier setup, Fig.…”
Section: Methodssupporting
confidence: 65%
“…Previous studies [16] have shown that these approximations are valid in the typical operational region of the SSRR, where T e /T e ≈U P /U P ≈ 1/25 (hc  ≈0.12 eV for =10.59 µm). Finally, the relationship between U OG…”
Section: Theorymentioning
confidence: 90%
See 3 more Smart Citations